Gastric Composite Tumor of Alpha Fetoprotein-Producing Carcinoma/Hepatoid Adenocarcinoma and Endocrine Carcinoma with Reference to Cellular Phenotypes. (5th March 2012) - Suzuki, Akira; Koide, Naohiko; Kitazawa, Masato; Mochizuka, Akiyoshi; Ota, Hiroyoshi; Miyagawa, Shinichi
Abstract : Alpha-fetoprotein-producing carcinoma (AFPC)/hepatoid adenocarcinoma (HAC) and neuroendocrine carcinoma (NEC) are uncommon in the stomach. Composite tumors consisting of these carcinomas and their histologic phenotypes are not well known. Between 2002 and 2007, to estimate the prevalence of composite tumors consisting of tubular adenocarcinoma, AFPC/HAC and NEC, we reviewed specimens obtained from 294 consecutive patients treated surgically for gastric cancer. We examined histological phenotype of tumors of AFPC or NEC containing the composite tumor by evaluating immunohistochemical expressions of MUC2, MUC5AC, MUC6, CDX2, and SOX2. Immunohistochemically, AFPC/HAC dominantly showed the intestinal or mixed phenotype, and NEC frequently showed the gastric phenotype. In the composite tumor, the tubular and hepatoid components showed the gastric phenotype, and the neuroendocrine component showed the mixed type. The unique composite tumor predominantly showed the gastric phenotype, and the hepatoid and neuroendocrine components were considered to be differentiated from the tubular component.